(x - 1)3 = 125
=> (x - 1)3 = 53
=> x - 1 = 5
=> x = 5 + 1
=> x = 6
(2x + 1)3 = 343
=> (2x + 1)3 = 73
=> 2x + 1 = 7
=> 2x = 7 - 1
=> 2x = 6
=> x = 3
720 : [41 - (2x - 5)] = 23.5
=> 720:[41 - (2x - 5)] = 40
=> 41 - (2x - 5) = 720 : 40
=> 41 - (2x - 5) = 18
=> 2x - 5 = 41 - 18
=> 2x - 5 = 23
=> 2x = 23 + 5
=> 2x = 28
=> x = 14
a) \(\left(x-1\right)^3=125\)
\(\Rightarrow\left(x-1\right)^3=5^3\)
\(\Rightarrow x-1=5\)
\(\Rightarrow x=5+1=6\)
b) \(\left(2\cdot x+1\right)^3=343\)
\(\Rightarrow\left(2\cdot x+1\right)^3=7^3\)
\(\Rightarrow2\cdot x+1=7\)
\(\Rightarrow2\cdot x=7-1\)
\(\Rightarrow2\cdot x=6\)
\(\Rightarrow x=6:2=3\)
c) \(720:\left[41-\left(2\cdot x-5\right)\right]=2^3\cdot5\)
\(720:\left[41-\left(2\cdot x-5\right)\right]=8\cdot5\)
\(720:\left[41-\left(2\cdot x-5\right)\right]=40\)
\(\Rightarrow41-\left(2\cdot x-5\right)=720:40\)
\(\Rightarrow41-\left(2\cdot x-5\right)=18\)
\(\Rightarrow2\cdot x-5=41-18\)
\(\Rightarrow2\cdot x-5=23\)
=> 2 . x = 23 + 5
=> 2 . x = 28
=> x = 28 : 2 = 14
a) ( x - 1 )3 = 125
=> ( x - 1 )3 = 53
=> x - 1 = 5
=> x = 6